Microvascular Rarefaction and Heart Failure With Preserved Ejection Fraction - Zeng, Heng; Chen, Jian-Xiong (Frontiers in Cardiovascular Medicine, 2019)
Heart failure with preserved ejection fraction (HFpEF) characterized with a diastolic dysfunction is common in the aging, diabetic and hypertensive patients. However, the pathophysiology of HFpEF is poorly understood and its optimal treatment remains undefined. Most recent clinic study indicates that coronary microvascular rarefaction is a major contributor to diastolic dysfunction in HFpEF patients. Endothelial cells (EC) utilize glycolysis for generating ATP rather than oxidative phosphorylation to maintain their normal functions and vascular homeostasis. Emerging evidence indicates that Sirtuin 3 (SIRT3) is involved in the regulation of endothelial glycolytic metabolism and thus affects angiogenesis. Disruption of SIRT3-mediated EC metabolism and impairment of angiogenesis may promote cardiomyocyte hypoxia and myocardial fibrosis, thus leading to a diastolic dysfunction and HFpEF. This review summarizes current knowledge of SIRT3 in EC metabolism, coronary microvascular dysfunction and HFpEF.